Analysis of the Role of Traditional Midwives in Maternal Health Services in Rural Areas - Qomariah, Hestiana; Winarsih, Ehti; Diana, Farida Mar (Trigin Institute, 2025)
This research explores the role of traditional midwives in maternal health services in rural areas, with a focus on their impact on prenatal care, delivery, and postnatal care. The study aims to assess the benefits, risks, and outcomes associated with traditional midwifery practices and examine how these midwives are perceived in their communities compared to formal healthcare providers. Using a mixed-methods approach, including qualitative interviews and surveys with local mothers, traditional midwives, and healthcare professionals, the research was conducted in Soban Village, Siempat Nempu District, Dairi Regency. Findings suggest that traditional midwives play a crucial role in providing accessible, culturally sensitive care, especially in remote areas where formal healthcare services are scarce. However, challenges such as limited formal training and integration with the formal healthcare system were identified as significant risks, particularly in cases of pregnancy complications or emergencies. The research highlights the need for policy frameworks that support the integration of traditional midwives into the formal healthcare system through training, collaboration, and community engagement. The study concludes that a hybrid model combining traditional midwifery practices with formal healthcare could improve maternal and neonatal health outcomes in rural communities.